Neuroprotective strategy for Alzheimer disease: intranasal administration of a fatty neuropeptide. - Gozes, I (1996)
Neurodegenerative diseases, in which neuronal cell disintegrate, bring about deteriorations in cognitive functions as is evidenced in millions of Alzheimer patients. A major neuropeptide, vasoactive intestinal peptide (VIP), has been shown to be neuroprotective and to play an important role in the acquisition of learning and memory. A potent lipophilic analogue to VIP now has been synthesized, [stearyl-norleucine17]VIP ([St-Nle17]VIP), that exhibited neuroprotection in model systems related to Alzheimer disease. The beta-amyloid peptide is a major component of the cerebral amyloid plaque in Alzheimer disease and has been shown to be neurotoxic. We have found a 70% loss in the number of neurons in rat cerebral cortical cultures treated with the beta-amyloid peptide (amino acids 25-35) in comparison to controls. This cell death was completely prevented by cotreatment with 0.1 pM [St-Nle17]VIP. Furthermore, characteristic deficiencies in Alzheimer disease result from death of cholinergic neurons. Rats treated with a cholinergic blocker (ethylcholine aziridium) have been used as a model for cholinergic deficits. St-Nle-VIP injected intracerebroventricularly or delivered intranasally prevented impairments in spatial learning and memory associated with cholinergic blockade. These studies suggest both an unusual therapeutic strategy for treatment of Alzheimer deficiencies and a means for noninvasive peptide administration to the brain.